2006
DOI: 10.1016/j.str.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of IRAK-4 Kinase in Complex with Inhibitors: A Serine/Threonine Kinase with Tyrosine as a Gatekeeper

Abstract: Interleukin-1 (IL-1) receptor-associated kinase-4 (IRAK-4) is a serine/threonine kinase that plays an essential role in signal transduction by Toll/IL-1 receptors (TIRs). Here, we report the crystal structures of the phosphorylated human IRAK-4 kinase domain in complex with a potent inhibitor and with staurosporine to 2.0 and 2.2 A, respectively. The structures reveal that IRAK-4 has a unique tyrosine gatekeeper residue that interacts with the conserved glutamate from helix alphaC. Consequently, helix alphaC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(164 citation statements)
references
References 50 publications
4
159
1
Order By: Relevance
“…Previously, Cheng et al (10) identified Thr-342, Thr-345, and Ser-346 by MS analysis, and other groups identified these residues by crystallography (19,22). In this report, we present several lines of evidence to support the hypothesis that autophosphorylation of IRAK4 is required for the full activation and subsequent signaling events in a cell type-specific manner.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Previously, Cheng et al (10) identified Thr-342, Thr-345, and Ser-346 by MS analysis, and other groups identified these residues by crystallography (19,22). In this report, we present several lines of evidence to support the hypothesis that autophosphorylation of IRAK4 is required for the full activation and subsequent signaling events in a cell type-specific manner.…”
Section: Discussionsupporting
confidence: 71%
“…We also examined primary human monocytes from healthy volunteers, because we were interested in innate immune cells where IRAK4 activity plays an important role as an inflammatory mediator. We used compound 1, a previously characterized inhibitor of IRAK4 kinase for our studies on the pharmacology of IRAK4 in human cells (19). This compound is highly potent against IRAK4 (IC 50 ϭ 2 nM at K m ϭ 300 M ATP) (22) and to a lesser extent IRAK1 (IC 50 ϭ 15 nM at K m ϭ 35 M ATP).…”
Section: Pharmacological Inhibition Of Irak4 Kinase Blocks Irak4 Phosmentioning
confidence: 99%
See 1 more Smart Citation
“…After submission of this manuscript, Wang et al (24) published the crystal structure of IRAK4 kinase domain complexed with staurosporine and a benzimidazole inhibitor.…”
Section: Two Kinase Domain Conformations and Implications On Irak4 Rementioning
confidence: 99%
“…As demonstrated previously, the kinase domain of IRAK-1 may adopt a tertiary structure that resembles the cyclin-dependent kinase. (28,58). Consequently, IRAK-1 preferentially phosphorylates substrate containing Ser/Thr-Pro-rich motifs.…”
mentioning
confidence: 99%